PERSEPSI MASYARAKAT TERHADAP AKTIVITAS PASAR KAGET DI JALAN CIPTA KARYA UJUNG KECAMATAN TAMPAN KOTA PEKANBARU - Aulia, Nurul; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at Jalan Cipta Karya Ujung District of Tampan, Pekanbaru City. The purpose of this study was to find out activities and analyze people's perceptions of Pasar Kaget activity  at Jalan Cipta Karya Ujung District of Tampan, Pekanbaru City. The focus of this research is about people's perceptions of Pasar Kaget at Jalan Cipta Karya Ujung District of Tampan, Pekanbaru City. Proporsional technique for sampling and determined a total sample of  30 traders and 87 buyers. The author uses quantitative descriptive methods and data instruments in this research are observation, questionnaires, and documentation. The study found that the Traders's Perception of Pasar Kaget activity on Cipta Karya Ujung Street which was higher was a negative perception with a percentage of 73.3%. And the buye’sr perception of the Pasar Kager activity on Cipta Karya Ujung Street wich was higher was a negative perception with the percentage of 79.3%. Keywords: Perception, Pasar Kaget